Third Five Year Plan First Year's Progress Report (1961-62) Government of Kerala - Planning Commission (Planning Commission, 1961)
The Third Five Year Plan of Kerala envisages an outlay of Rs. 170 00 crores, which is nearly double the size of the Second Plan I for the first year (1961-62) of the Third Plan was Rs. 2,815.32 lakhs including the Central share on Centrally sponsored schemes the share of the I. C. A. R. and Central Commodity Committees for the schemes sponsored by them and the share of E. S. I. Corporation for the E. S. I. Scheme.
Government of Kerala, Planning Department